Red, Yellow, Or Green: Which Colors Are Your Co-Operatives? - Novita Puspasari; Meutia Karunia Dewi; Tiladela Luhita (EKO-REGIONAL, 2020)
Co-operative is a socio-economic institution which is the most appropriate for Indonesian economic system. Indonesia has the largest number of co-operatives in the world, however, they have not contributed optimally for the Indonesian economy. Co-operative trainings held by the government failed to improve co-operative’s quality, since those trainings were not based on co-operative’s real needs. This study aims to identify and map areas of action for future development of the co-operatives. Using modified Development Ladder Assessment (DLA) as a tool, 74 co-operatives in Central Java, Indonesia,  were measured. Four dimensions were assessed using DLA: 1) vision, 2) governance and member engagement, 3) management capacity and business development, and 4) financial management.  Total score for each dimension determines whether co-operative is in red, yellow or green areas. Red means poor, yellow means moderate, and green means excellent. Most of the co-operatives are poor in the first (vision) and the third (management capacity and business development) dimensions. The Co-operatives were also found to have moderate governance and member engagement (the second dimension). Finally, the result show that financial management (the fourth dimension) has been well-implemented. Implication of this study is that co-operatives are suggested to get appropriate trainings based on their color areas.